Highway Politics in Virginia - Bowman, Gary M. (University Press Copublishing Division, 1992)
Bowman describes Governor Gerald L. Balies' attempt to address the transportation problems caused by rapid suburban growth by reorienting the highway program from rural to suburban areas. He describes the political background and the political consequences of the program change. This is the only recent analysis of a state's attempt to change its approach to highway policy and the only analysis of highway politics of any American state.